2021
DOI: 10.3390/cryst11060689
|View full text |Cite
|
Sign up to set email alerts
|

Stress–Strain Behavior of FRC in Uniaxial Tension Based on Mesoscopic Damage Model

Abstract: Fiber-reinforced concrete (FRC) is widely used in the field of civil engineering. However, the research on the damage mechanism of FRC under uniaxial tension is still insufficient, and most of the constitutive relations are macroscopic phenomenological. The aim is to provide a new method for the investigation of mesoscopic damage mechanism of FRC under uniaxial tension. Based on statistical damage theory, the damage constitutive model for FRC under uniaxial tension is established. Two kinds of mesoscopic damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The mechanical properties and durability of concrete are significantly influenced by its microstructure, where internal defects such as pores and microcracks can be detrimental. 8 This further illustrates the necessity of refining the pores and cracks in SCC. Generally, supplementary cementitious materials such as fly ash (FA), ground granulated blast furnace slag (GGBFS) and metakaolin are all micron-sized materials, and the particle size is usually tens of microns.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The mechanical properties and durability of concrete are significantly influenced by its microstructure, where internal defects such as pores and microcracks can be detrimental. 8 This further illustrates the necessity of refining the pores and cracks in SCC. Generally, supplementary cementitious materials such as fly ash (FA), ground granulated blast furnace slag (GGBFS) and metakaolin are all micron-sized materials, and the particle size is usually tens of microns.…”
Section: Introductionmentioning
confidence: 92%
“…At the same time, researchers are constantly exploring ways to improve the overall performance of SCC. The mechanical properties and durability of concrete are significantly influenced by its microstructure, where internal defects such as pores and microcracks can be detrimental 8 . This further illustrates the necessity of refining the pores and cracks in SCC.…”
Section: Introductionmentioning
confidence: 99%
“…The Modified Drucker-Prager yield criterion is used with consideration of Lubliner Model (Lubliner, 1989) and damaged plasticity model (Lee and Fenves, 1998) for concrete and other quasi-brittle materials. This concrete damaged plasticity model has been widely used for RC and FRC application in both static and dynamic situation [31][32][33][34]. The volume fraction of SF was set to 0.76% (l f = 33 mm, d f = 0.55 mm).…”
Section: Finite Element Modelsmentioning
confidence: 99%
“…In Shi et al [ 4 ], it is shown how the fibers clearly affect the matrix post-cracking behavior. While Bai et al [ 5 ] analytically studied how the tensile behavior changes as the fiber content changes, as well as the effects of this parameter on the initiation and expansion of microcracks. Studies have also been conducted on the response of FRCM material in presence of different environmental conditions [ 6 ], effects of rising damp and salt crystallization cycles [ 7 ] and with the effect of the wet-dry cycle [ 8 ].…”
Section: Introductionmentioning
confidence: 99%